Petrogenesis of the upper critical zone in the Western Bushveld Complex with emphasis on the UG1 Footwall and Bastard units - De Klerk, William Johan (Rhodes University, Faculty of Science, Department of Geology, 1992)
This study is an account of the stratigraphic sequence, the petrography, mineralogy (microprobe investigations of orthopyroxene, clinopyroxene, olivine and plagioclase feldspar), and whole-rock major- and traceelement geochemistry of the silicate cumulates of the Upper Critical Zone in the western Bushveld Complex. Two parts of the study - an investigation of a 350m column incorporating the MG3 and UGI Footwall Units, and a comparison of two additional Upper Critical Zone profiles with a previously compiled profile between the UGI and Bastard Units - are focused on RPM Union Section in the northwestern sector of the Complex. The third part is a detailed vertical and lateral investigation of the Bastard Unit at the top of the Critical Zone, which draws on sampling and data compilation from seventeen profiles in the western limb of the Complex. The MG3 Unit (45m) is made up of a lower chromitite layer overlain by a norite-pyroxenite-anorthosite sequence while the UGlFW Unit (295m) is composed of a related series of lower chromitite layers (MG4) overlain by a pyroxenite-norite-anorthosite sequence capped by the UGI chromitite layer. These mafic cumulates display a distinctive pattern of oscillating cryptic variation in whole-rock Mg/(Mg+Fe), FeO/Ti0â‚‚, Cr/Co and Ni/V ratios through the sequence. Sympathetic oscillations are recorded for compositions of orthopyroxene and plagioclase feldspar and eight subcycles are recognised through the UGlFW Unit. The entire sequence is characterised by the presence of small, spheroidal, embayed and irregularly shaped plagioclase grains which are poikilitically enclosed in cumulus orthopyroxene grains of both pyroxenites and norites. This texture is indicative of partial resorption of pre-existing feldspar primocrysts within the melt prior to their being incorporated into the host orthopyroxene grains. Textural, geochemical and isotopic data suggest that this sequence was built up by periodic additions of fresh, relatively primitive liquid into fractionated resident liquid, and subsequent mixing within the magma chamber. The Bastard Unit sequence, described in Chapter 4, is the last and most complete cyclic unit (c. 60m) of the Critical Zone, and its upper contact defines the boundary between the Critical and Main Zones of the Complex. This Unit can conveniently be sub-divided into a lower part, where orthopyroxene occurs as a cumulus phase, and the upper part which is composed entirely of anorthosite (Giant Mottled Anorthosite). The basal part of the Unit (â‰¤ 18m) comprises a thin chromitite layer < O.5cm) overlain by a pyroxenite-melanorite-norite-leuconorite sequence. The basal pyroxenite is orthocumulate in character and rapidly gives way to norites and leuconorites. A distinct threefold subdivision emerges within the Giant Mottled Anorthosite which is predominantly an adcumulate which becomes orthocumulate in character at its top. Apart from minor deviations in thicknesses these lithologies are recorded over the entire strike-length covered in this study. Profiles of cryptic variation are compiled for orthopyroxene, plagioclase and whole-rock data and show that the Bastard Unit displays a characteristic pattern which is maintained throughout the western Bushveld Complex. A minor yet distinctive reversal in cryptic variation is revealed at a level which is stratigraphically variable within the lower Giant Mottled Anorthosite, and results in a double cuspate pattern. A remarkable feature of the basal Bastard pyroxenites is that although the modal proportion of mafic to felsic constituents varies systematically away from the northwestern sector, the Mg/(Mg+Fe) ratio of orthopyroxenes remains constant at 0.804 over a lateral strike distance of 171km. Within the upper part of the Unit the orthopyroxene is markedly Fe-rich and it is here that inverted primary pigeonite appears for the first time as a cumulus phase. In addition, K-feldspar, oscillatory zoned plagioclase grains and high levels of incompatible trace elements are noted at this level. On the basis of the data presented it is concluded that the Bastard Unit represents the crystallisation of a final, relatively large influx of hotter primitive liquid, with upper Critical Zone affinities, and subsequent mixing with a column of cooler (less dense) supernatant liquid which had in part hybridized with the overlying Main Zone magma. It is hypothesised that this new liquid was emplaced as a basal flow beneath supernatant liquid and that it initiated the deposition of mafic cumulates at its base. The supernatant liquid is interpreted as representing the fractionated residuum produced by crystallisation of earlier cyclic units, with plagioclase on the liquidus, and that it contained an abundance of small plagioclase primocrysts in suspension. Development of the Unit can be viewed as a two-stage process. In the lower half of the unit, chemical and physical parameters typical of the new magma dominated the crystallisation process, and resulted in cumulates very similar to other relatively complete Upper Critical Zone units. In the upper, leucocratic sequence, above a minor reversal, crystallisation was from a liquid which was the product of mixing of a minor pulse of primitive liquid with the reservoir of hybridized supernatant liquid. Although the Bastard Unit is not continuous around the entire Western limb of the Complex, it is concluded that it developed in a single, or connected, magma chamber and that its irruptive feeder zone was located in the proximal northwestern facies of the Complex.
Keywords: Petrogenesis -- South Africa; Formations (Geology) -- South Africa; Mineralogy -- South Africa; Geochemistry -- South Africa; Petrology -- Africa, Southern; Rustenburg Platinum Mines